Pelaksanaan Mediasi dalam Menyelesaikan Perkara Perceraian di Pengadilan Agama Tanjung Pati Tahun 2023 Perspektif Fiqh Munakahat - Tiansi Lasamudra; Hendri Hendri (AHKAM, 2026)
This study was motivated by the high number of divorce cases at the Tanjung Pati Religious Court and the importance of the mediation techniques and processes conducted by mediator judges in resolving these cases. This study aimed to analyze the mediation process in resolving divorce cases at the Tanjung Pati Religious Court and to examine its implementation from the perspective of fiqh munakahat. This study was field research with a descriptive qualitative approach. Data were collected through interviews and direct observation of mediator judges at the Tanjung Pati Religious Court and then analyzed qualitatively in descriptive form. The results showed that the stages of mediation in resolving divorce cases at the Tanjung Pati Religious Court were in accordance with the stages of mediation as regulated in PERMA No. 1 of 2016. In addition, the concept of reconciliation or as-sulh from an Islamic perspective is consistent with the concept of mediation in court, as reflected in the principle of dispute resolution through reconciliation. In the context of fiqh munakahat, the resolution of disputes between husband and wife is also consistent with the provision on appointing hakam from the families of both the husband and the wife to reconcile the two parties. The conclusion of this study emphasizes that the implementation of mediation at the Tanjung Pati Religious Court not only has a juridical basis under PERMA No. 1 of 2016 but also has normative relevance to the principle of reconciliation in fiqh munakahat. These findings imply the importance of optimizing the role of mediator judges in strengthening reconciliation efforts in divorce cases within the religious court system.